Successes and challenges of implementing a teacher education project in rural Sierra Leone. (2015) - McDermott, Peter; Allen, Nancy
Highlights: We examine a literacy education project for school leaders in rural Sierra Leone. Participants developed in their knowledge and use of literacy methods. They reported success at implementing workshops in their rural areas. Insufficient resources and travel conditions challenged the project. Some teachers lacked formal education and this presented other challenges. Abstract: This study examined the successes and challenges of implementing a teacher education project that was designed to improve methods of teaching reading and writing in rural Sierra Leone. Thirty school leaders representing five chiefdoms participated in three five-day workshops, which were held over the course of the 2013–2014 academic year. After completing each of the weeklong workshops, the school leaders were expected to provide similar workshops for teachers in their regions. The hope was that in this way the project's impact would be increased. Research questions pertained to the school leaders' perceptions about their learning of the workshop's literacy methods and eliciting their thoughts about the successes and challenges of project implementation in their regions. Multiple data sources were used, including informal interviews, pre–post surveys, document analyses and classroom observations. Our findings indicated that the school leaders improved significantly in their self-reported knowledge and use of literacy methods. They reported they successfully implemented local workshops, and their participants were receptive and eager to learn and use the teaching methods in their schools. The school leaders reported significant challenges, however, in implementing local workshops because of insufficient classroom resources, difficult travel conditions to the school sites and a lack of formal education of many of the teachers. Findings are discussed within the context of this developing country as it continues to rebuild its school system from the civil war, overcome severe economic hardships and manage a deadly virus that is currently interfering with everyday life, including classroom teaching and learning.